Adsorption and Complexing Properties of Silicas with Analytical Reagents Grafted via the Mannich Reaction - E.S. Yanovska; V.A. Tertykh; O.Yu. Kichkiruk; A.D. Dadashev (Adsorption Science & Technology)
The pre-concentration of metal ions such as Pb(II), Cd(II), Zn(II), Hg(II) and Mo(VI) on silicas with covalently bound 8-hydroxyquinoline, 1-(2-pyridylazo)-2-naphthol or 4-(2-pyridylazo)resorcinol has been studied. The structures of metal-ion complexes with grafted phenolic-type analytical reagents were investigated by IR, ESR and electronic diffuse reflectance spectroscopies.